Development Of Pop Up Book Media Sub Theme Technology Development Of Clothing Production To Train Writing Skills In Class III Elementary School Students - Sa’adah, Sufi Ikrima; Wibowo, Satrio; Rahmawati, Ery (Universitas Negeri Malang, 2022)
In the development of this Pop Up Book media using 7 procedures, namely potential and problems, from the results of potential and problems then the researcher conducts and makes a data collection, from the data collection the researcher makes a design design that will be validated by media experts and if there is a revision it will be corrected immediately, after that it will be tested, if there are still deficiencies it will be revised again so that the resulting product is ready to be used in learning. The development of this Pop Up Book media aims to train the writing skills of third grade elementary school students. Research and Development (R&D) is the method that will be used in this research by using pretest-posttest. In this study, the subjects used were third grade students in the 2021/2022 academic year, totaling 14 students as controls and 14 students as experimenters. Learning outcomes after using Pop Up Book media obtained the final results online for each class, namely in the control class, namely 47%, which is stated in the control class is included in the category of